O glossário como instrumento de desenvolvimento em contexto de ensino de matemática - Silveira, Maria Helena (2010)
This thesis aims to evaluate the role of language in the activity of elaborating a glossary with algebraic initial terms in an elementary classroom. The research was developed on mathematic classes ministered by the teacher-researcher to 6th grade students in 2006, and to the same class in 2007, this time on 7th grade. The glossary of algebraic terms was produced based on the students search for words in the didactic book used by the school. The senses attributed by the students to express the initial concepts of algebra were analyzed, as well as the collaborative method of research, based on Magalhães (2004, 2007, 2009). The glossary was structured according to the needs of the learning moment in conformity to the discussions of Vygotsky (1930/2002) about the centrality of the mediator instrument in learning and development. The theoretical background is supported by the discussions of the Social-Historical-Cultural Activity Theory, emphasizing Vygotsky s contributions on sense and meaning and ZPD, as well as by the studies of Leontiev (1978), Newman and Holzman (1993/2002), and Engeström (2001). This thesis is inserted in the Applied Linguistics area, under the research line Language and Education, from the Pontifícia Universidade Católica de São Paulo. The starting point was the relation between theory/practice in organizing the work into the classroom, based on the comprehension that the object s expansion teaching-learning in algebra occurs in and through the language. The research corpus is constituted of transcriptions of mathematics classes, student s exercise books with the glossary production and texts about their learning during the process, and the researcher s field diary. The linguistic-discursive analysis revealed that the instrument usage propitiated the students comprehending the senses and sharing the meanings of algebraic terms. The glossary elaboration also enabled an effective commitment of the students in the activity, contributing to addressing the difficulties in mathematics learning, situated within the language of the students, of the didactic book, the teacher and mathematics. This way, the glossary represented a concrete possibility of participation to the students, creating also spaces to the protagonism of their own actions, which brought empowerment and autonomy. The language as a mediator on senses and meanings construction by the activity participants and the appropriation of the glossary as an instrument were considered the central contribution to the interface Applied Linguistics Mathematics, which enabled a creative praxis instead of a routined and reiterative one